ASSESSMENT IN INTENSIVE LANGUAGE TEACHING. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the role of assessment in intensive language teaching. It explores different types of assessments—diagnostic, formative, summative, and performance-based—and discusses their application in fast-paced, immersive language learning environments. The article also highlights the importance of continuous feedback, adaptability, and learner-centered assessment to support rapid and effective language acquisition.